2016
DOI: 10.1152/jn.00964.2015
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable saccadic suppression of pupillary and perceptual responses to light

Abstract: We measured pupillary constrictions in response to full-screen flashes of variable luminance, occurring either at the onset of a saccadic eye movement or well before/after it. A large fraction of perisaccadic flashes were undetectable to the subjects, consistent with saccadic suppression of visual sensitivity. Likewise, pupillary responses to perisaccadic flashes were strongly suppressed. However, the two phenomena appear to be dissociable. Across subjects and luminance levels of the flash stimulus, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
14
2
Order By: Relevance
“…We choose not to measure pupil dynamics during binocular rivalry, but in a separate session with no visual stimulation. This choice is motivated by prior work showing that pupil size is sensitive to the dynamics of binocular rivalry [40, 41] and that pupil responses to visual stimuli may be larger/smaller when the stimulus representation in the visual cortex is enhanced/suppressed, for example, enhanced during focused attention [4246] or suppressed during saccadic eye movements [47, 48]. Thus, it is expected that pupil behavior during binocular rivalry changes after MD, simply as a result of its modifying the rivalrous interplay between the eyes [2] and affecting cortical responses to the deprived eye [1].…”
Section: Introductionmentioning
confidence: 99%
“…We choose not to measure pupil dynamics during binocular rivalry, but in a separate session with no visual stimulation. This choice is motivated by prior work showing that pupil size is sensitive to the dynamics of binocular rivalry [40, 41] and that pupil responses to visual stimuli may be larger/smaller when the stimulus representation in the visual cortex is enhanced/suppressed, for example, enhanced during focused attention [4246] or suppressed during saccadic eye movements [47, 48]. Thus, it is expected that pupil behavior during binocular rivalry changes after MD, simply as a result of its modifying the rivalrous interplay between the eyes [2] and affecting cortical responses to the deprived eye [1].…”
Section: Introductionmentioning
confidence: 99%
“…Motor-related signals (like anticipatory intention-to-move signals or corollary discharge) are available before the actual execution of a movement and may thus serve as endogenous predictive cues, to inform the sensory systems about the upcoming inputs. Traditionally, these anticipatory signals have been conceived to counteract the disruptive side-effects of movement on perception by selective sensory suppression, and may participate in the mechanism mediating perceptual stability by updating and remapping spatial information across movements (Benedetto & Binda, 2016;Binda & Morrone, 2018;Burr & Morrone, 2011;Crapse & Sommer, 2008;Diamond, Ross, & Morrone, 2000;Duhamel, Colby, & Goldberg, 1992;Medendorp, 2011;Ross, Morrone, Goldberg, & Burr, 2001). A corollary discharge signal may also operate as a momentary boost of perceptual sensitivity to optimize processing of the new sensory inflow brought about by the movement itself (Binda & Morrone, 2018;Knöll, Binda, Morrone, & Bremmer, 2011;Melloni, Schwiedrzik, Rodriguez, & Singer, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This result was soon replicated (33) and other studies began finding that the PLR depended on visual processing in other ways. For example, a stimulus detection study found that the PLR was absent for probes reported as not seen (34) and a presaccadic processing study found that the likelihood of evoking a PLR was suppressed before a saccade (35)—following a similar time course as the presaccadic suppression of visual perception [also see (36)]. One unifying interpretation of these observations is the idea that the PLR is modulated by visual attention.…”
Section: Attention and The Pupil Light Responsementioning
confidence: 99%